Integration between location based service (LBS) and online analytical processing (OLAP): semantic approach - Halim, A.H.A.; Ismail, M.A.; Ravana, S.D. (2008)
Location Based Service (LBS) LBS are mobile service that has the capability to provide real time information basedon the user's location. Geographical Information System (GIS) has been the heart of LBS in order to provide all the functionalities in LBS. Although mostly transparent, GIS provides the basis for most functionality, from services like geocoding, routing, location search to map presentation in LBS. In the Knowledge Discovery realm, Spatial Online Analytical Processing (SOLAP) integrates conventional OLAP with GIS data sets .Integration of these two heterogeneous data sources deals with issues such as different data model structures, different schemas and query languages. In the implementation of SOLAP, two different data model must be considered. Geographical Information System (GIS) describes its data model in a hierarchical structure, use to represent spatial features. Online Analytical Processing (OLAP) however describes its data in a multi-dimensional structure, known for fast analytical processing. Although having such differences, it is now possible to distribute the data available from these three systems (LBS, GIS, OLAP) in the web. The internet has become the main transport for data and information exchange, and a proper integration framework should be use. This paper explains the process of data integration in LBS and SOLAP using Semantic Web Technology.